Risk aggregation for nuclear installations. (IAEA-TECDOC ;, 2021)
"This publication describes the practices and challenges related to risk aggregation for various hazards, various operational states, and considering all sources of potential radioactive releases at a nuclear installation site. It provides a methodology and technical basis for risk aggregation and describes the good practices and practical examples of risk aggregation developed by IAEA Member States. The description of practices is supplemented by the detailed discussion on risk communication and use of aggregated risk results to support decision making processes."--Publisher's description.